Determination Of Heat Transfer Coefficients In Heat Exchangers By Genetic Algorithm - Tan Boon Tat, Boon Tat (Universiti Teknologi Petronas, 2010)

(untitled)
Genetic algorithm (GA), developed by John Holland in the 1970s, is gaining widespread attention throughout the years. In particular, GA is being extensively used in the field of optimization. This paper discusses the utilization of GA in estimating the coefficients and exponents in developing the Nusselt Number correlation in two different heat exchanger geometries, with the aim to reduce the error incurred in predicting heat transfer coefficients and heat transfer rates. With such reduction, for instance, the design of heat exchangers can be more compact, incurring less cost in the process.